Elementary school parent engagement efforts: Relations with educator perceptions and school characteristics. Issue 4 (4th July 2017) - McDowall, Philippa S.; Schaughency, Elizabeth
Abstract: School efforts to engage parents are posited to influence whether and how they are involved in their children's schooling. The authors examined educators' engagement efforts in beginning reading, their subjective evaluations of engagement practices, and beliefs about parent involvement, in two stratified samples of New Zealand elementary school educators. They explored whether educators' ratings supported multidimensional and multitiered theoretical models of engagement. The authors invited responses from elementary principals and teachers, given their different roles in the nested ecology of schools and relationships with parents, and examined associations between pairs of principals and teachers working in the same school. Finally, the authors examined relations among educators' engagement efforts, evaluations of engagement practices, and beliefs about involvement, and school characteristics including community socioeconomic status, size of school population, ethnic composition of school population, community size, and geographic region.